2021
DOI: 10.1071/cp20445
|View full text |Cite
|
Sign up to set email alerts
|

Carbon and nitrogen metabolism in rice cultivars affected by salt-alkaline stress

Abstract: Salt-alkaline stress generally leads to soil compaction and fertility decline. It also restricts rice growth and nutrient acquisition, so reduces rice yield. However, little is known about the effect of salt-alkaline stress on the carbon and nitrogen metabolism of rice. In this study, two relatively salt-alkaline tolerant (Changbai 9 and Dongdao 12) and sensitive (Jinongda 138 and Tongyu 315) rice cultivars were grown in a field experiment conducted with two soil types including black soil and salt-alkaline so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…Improving NUE under salt stress is critical for plants, as they are increasingly confronted with two major environmental constraints: excessive N fertilization and soil salinization. Several studies have been conducted to assess NUE under saline conditions (Song et al, 2019;Guo et al, 2021;Phan et al, 2022; Table 1). It has been proposed that NUE can be determined by agronomic NUE (aNUE), physiological NUE (pNUE), internal NUE (iNUE) and N recovery efficiency (NRE) which gets affected by salt stress.…”
Section: Regulation Of Nitrogen Metabolism and Nitrogen Use Efficienc...mentioning
confidence: 99%
See 1 more Smart Citation
“…Improving NUE under salt stress is critical for plants, as they are increasingly confronted with two major environmental constraints: excessive N fertilization and soil salinization. Several studies have been conducted to assess NUE under saline conditions (Song et al, 2019;Guo et al, 2021;Phan et al, 2022; Table 1). It has been proposed that NUE can be determined by agronomic NUE (aNUE), physiological NUE (pNUE), internal NUE (iNUE) and N recovery efficiency (NRE) which gets affected by salt stress.…”
Section: Regulation Of Nitrogen Metabolism and Nitrogen Use Efficienc...mentioning
confidence: 99%
“…Furthermore, NUE was significantly reduced in the salt-sensitive genotype of Avena sativa (oat) compared to tolerant genotype (Song et al, 2019). Recently, Guo et al (2021) revealed that salt stress significantly reduced N metabolism, NUE, and grain yield in rice seedlings. Effective crop management practices and smart decision-making are required to ensure high crop yields under salt stress conditions and meet increasing global food security.…”
Section: Regulation Of Nitrogen Metabolism and Nitrogen Use Efficienc...mentioning
confidence: 99%
“…46 Increased soil salinity leads to soil compaction and a reduction in plant growth, nutrient acquisition and yield due to altered carbon and nitrogen metabolism. 47 High salt concentrations negatively impact the physiology and development of plants by disturbing cellular ion balance, causing osmotic loss, disturbing membrane integrity and increasing the production of reactive oxygen species. Adopting suitable agronomic strategies to mitigate the impact of salt stress and identifying salt-tolerant varieties is the key to developing resilience in agricultural systems.…”
Section: Salinity Stressmentioning
confidence: 99%
“…Carbon and nitrogen metabolism were closely related, and their degree of coordination not only affected the growth and development process but also affected yield and quality of crops (Guo et al, 2021;Cheng et al, 2019). Long-term warming in cool region can improve rice yields in three ways (Fig.…”
Section: The Effect Of Physiological Response Of Rice On Yield Under ...mentioning
confidence: 99%